Role theory : expectations, identities, and behaviors - Biddle, Bruce J. (Bruce Jesse), 1929-2016 (Academic Press, 1979)
Role Theory: Expectations, Identities, and Behaviors presents the applications of role concepts for education, social work, and clinical practice. This book examines the advantages as well as the shortcomings of the role stance. Organized into nine chapters, this book begins with an overview of behaviors that are characteristics of persons within contexts and the various processes that are employed to explain and predict those behaviors. This text then examines the concepts of the role field and discovers their applications to social problems of pressing concern. Other chapters consider the empirical evidence that has been developed within the role orientation concerning social problems. This book discusses as well the behavioral comparability, behavior linkage, behavioral effects, and complex linking concepts for behaviors. The final chapter discusses how contexts may affect the behaviors of persons and how those behaviors may have subsequent functions. This book is a valuable resource for anthropologists, sociologists, and social psychologists